The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s11065-023-09589-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Neuropathophysiological Outcomes of Gamma-tACS in Dementia: A Systematic Review

Abstract: Despite the numerous pharmacological interventions targeting dementia, no disease-modifying therapy is available, and the prognosis remains unfavorable. A promising perspective involves tackling high-frequency gamma-band (> 30 Hz) oscillations involved in hippocampal-mediated memory processes, which are impaired from the early stages of typical Alzheimer’s Disease (AD). Particularly, the positive effects of gamma-band entrainment on mouse models of AD have prompted researchers to translate such findings int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 142 publications
(207 reference statements)
0
4
0
Order By: Relevance
“…Second, the study's reliance on a single tACS session could limit the detection of enduring or robust stimulation effects. Drawing from previous research (Manippa et al, 2023), multiple sessions of tACS may produce cumulative effects. Therefore, future studies should consider multiple stimulation sessions to capture the potential in uence of HD-tACS on optimistic belief updating.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the study's reliance on a single tACS session could limit the detection of enduring or robust stimulation effects. Drawing from previous research (Manippa et al, 2023), multiple sessions of tACS may produce cumulative effects. Therefore, future studies should consider multiple stimulation sessions to capture the potential in uence of HD-tACS on optimistic belief updating.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tDSC and tACS have existed in the niche theme of Figure 4, but they are growing topics in the neuroscience literature. [65,66]. The one direction for future research is bibliographic analysis of special statistical methods with EEGLAB and EEG datasets for example, machine learning methods such as support vector machine [67], dimension reduction methods such as ICA [43] , functional data analysis methods [68,69], and deep learning methods [17,70].…”
Section: Discussionmentioning
confidence: 99%
“…While significantly better established clinically, only two studies utilized TMS, though both demonstrated a positive effect of multiple TMS sessions per week, over 2–6 weeks, targeting DLPFC/parietal areas, or precuneus, on coupling of gamma activity across distributed cortical networks, WM and trail making [ 80 , 83 ]. That TACS, despite being much less well established clinically, exhibits greater popularity than TMS likely arises from TACS being significantly more cost-effective, portable and accessible [ 12 ]. Furthermore, while rare, TMS nevertheless exhibits significantly higher seizure risk than TACS, a potentially serious risk in older patients with neurologic decline [ 85 , 86 ].…”
Section: Recent Studies Testing Gamma Neuromodulation As Treatment Fo...mentioning
confidence: 99%